Analisis pengembangan kurikulum berbasis kompetensi (studi kurikulum program studi muamalah jurusan syariah dan ekonomi islam STAIN Samarinda) - Darmawati, Darmawati; Parno, Parno (FENOMENA, 2013)
The aim of this research are to know objective condition of curriculum at Muamalah Courses now (that still be used now) and to know development of curriculum based on stakeholders needs. Analysis model that be done is interactive analysis, with four components: data reduction, data display, conclusion and verification doing by simultaneously. The result is both in term of design, implementation and evaluation still need reviewed and assessed comprehensive and completely based on stakeholders needs.